2018
DOI: 10.5152/etd.2018.0140
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of early childhood masturbation in a case of autism spectrum disorder: a case report

Abstract: While there have been several reports concerning the treatment of inappropriate sexual behaviors in children with autism spectrum disorder (ASD), there have been no reports concerning treatment of childhood masturbation in subjects with ASD aged <3 years. We describe a 30-month-old girl referred to our department due to language delay, behavioral problems, and lower-limb contractions. She was diagnosed with ASD according to the Diagnostic and Statistical Manual of Mental Disorders (5th Edition) criteria and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In adolescents with ASD the attitude that must be done by parents in dealing with this activity is to provide opportunities, provide privacy and teach children not to do this activity in public. [35][36][37] Our research also reveals the unique unexpected behaviors exhibited by adolescents with ASD while in love such as imagining the opposite sex, expressing feelings with pictures, holding the body of the opposite sex, showing jealousy by hitting. These signs indicate that parents of teenagers with ASD need a good sexual education to be able to direct the behavior as described above following adolescent development.…”
Section: Discussionmentioning
confidence: 94%
“…In adolescents with ASD the attitude that must be done by parents in dealing with this activity is to provide opportunities, provide privacy and teach children not to do this activity in public. [35][36][37] Our research also reveals the unique unexpected behaviors exhibited by adolescents with ASD while in love such as imagining the opposite sex, expressing feelings with pictures, holding the body of the opposite sex, showing jealousy by hitting. These signs indicate that parents of teenagers with ASD need a good sexual education to be able to direct the behavior as described above following adolescent development.…”
Section: Discussionmentioning
confidence: 94%
“…2,15 Furthermore, in cases of gratification disorder unresponsive to behavioral management, various psychopharmacological agents such as selective serotonin reuptake inhibitors (escitalopram) and antipsychotics (risperidone, aripiprazole) were recommended in other literatures. [18][19][20] The mechanism of action of these medications was reported to be decrement in dopamine in mesolimbic system through D2 and 5-HT2 receptors. No pharmacotherapeutic intervention was done in the abovementioned cases since all the cases responded significantly to behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because sexual behaviors trouble the caregiver, family and community, treatment become more important. There are studies shown the ineffectiveness of psychoeducation and behavioral interventions [12]. Pharmacological treatments could be preferred in those cases.…”
Section: Discussionmentioning
confidence: 99%